Death and Rebirth of Atlántida: The Role of Social Learning in Bringing about Transformative Sustainability Processes in an Ecovillage - Martha Chaves; Thomas Macintyre; Eliana Riano; Jorge Calero; Arjen Wals (Environmental Association of Southern Africa, 2016)
This paper explores the role of social learning in bringing about transformative sustainability processes among individuals and communities. At a time when sustainability is being seriously questioned in terms of what it is and how it can be implemented and evaluated, there are increasing calls to focus instead on sustainability processes. Drawing on 12 months of action-oriented research, including interviews and community-reflection meetings, and with contributions by two co-researchers from the community studied, this paper explores the triple-loop learning process of an ecovillage in Colombia called Atlántida. The findings show that disruptions in the community provided the opportunity for members to enter into a process of deep learning, because they were willing to reflect collectively on their process. This, however, took place in a tough reflective environment in which it was realised that differences in world views, ethics and leadership among members had contributed to the 'death' of the community, while their acknowledgement and acceptance of these differences were contributing to a process of transformative 'rebirth.' We therefore conclude that, when we talk about social learning as a deep transformative process, it is vital to remember that, though it may be necessary, nobody said it was going to be easy.